Psychometrics as a Tool to Improve Credit Information - Arraiz, Irani; Bruhn, Miriam; Stucchi, Rodolfo (Published by Oxford University Press on behalf of the World Bank, 2019)
This paper studies the use of psychometric tests, designed by the Entrepreneurial Finance Lab (EFL), as a tool to screen out high credit risk and potentially increase access to credit for small business owners in Peru. We compare repayment behavior patterns across entrepreneurs who were offered a loan based on the traditional credit scoring method versus the EFL tool. We find that the psychometric test can lower the risk of the loan portfolio when used as a secondary screening mechanism for already banked entrepreneurs—that is, those with a credit history. The EFL tool can also allow lenders to offer credit to some unbanked entrepreneurs—that is, those without a credit history—who were rejected based on their traditional credit scores, without increasingthe risk of the portfolio.